Gastropulmonary Fistula after Bariatric Surgery - Maya Doumit; Gaby Doumit; Farid M Shamji; Sylvie Gregoire; Richard E Seppala (Canadian Journal of Gastroenterology)
The Roux-en-Y gastric bypass is one of the most common operations for morbid obesity. Although rare, gastropulmonary fistulas are an important complication of this procedure. There is only one recently reported case of this complication. The present report describes the serious nature of this complication in a patient after an uneventful laparoscopic gastric bypass surgery.